Ngaben sebagai Daya Tarik Pariwisata - Ida Ayu Tary Puspa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2019)
The Ngaben ceremony is included in the pitra yadnya ceremony, namely the ceremony of burning the corpse accompanied by upakara / banten and Pandita (sulinggih). The ceremony is accompanied by facilities such as bade as a place for carrying the corpse to the grave / setra and sometimes also equipped with oxen and naga banda for the main category of ngaben as is done at Puri Ubud. This Ngaben ceremony is included in the attraction of ritual tourism and religious activities because it is so interesting to witness so that tourists experience such experiences in the tourist areas they visit.